Desempenho de bananeiras irrigadas em resposta a diferentes profundidades efetivas do solo na Chapada do Apodi - CE - Miotti, Alan Antonio (2011)
The production of banana can be affected whether plants are cropped in sites with physical impedances, as those found in shallow soils. The aim of this research was to verify if irrigated banana plants performance is affected by effective soil depth, and for this purpose were evaluated both soil physical and chemical attributes, as well as plants nutritional condition, root system, and attributes related with banana plants yield. The study was carried out at Apodi Plateau (CE), by evaluation of two treatments: shallow and deep soils. Soil samples (indisturbed and disturbed) and roots were collected in six soil depths (0-10, 10-20, 20-30, 30-40, 40-50 e 50-60 cm) and five replications. In undisturbed samples were determined soil physical attributes like water retention curve (CR), soil bulk density (Ds), and porosity (PT). In the disturbed samples were analized soil texture, particles density (Dp), besides chemical determinations for soil fertility purposes. Soil penetration resistance was evaluated directely in the field, using an impact penetrometer, with five replications and until soil depth of 60 cm. To root studies the sampling was done using a probe, and after collecting, samples were washed to separate roots from soil. From washed root images were evaluated attributes like root lenght, area and total volume, besides root diameter classes. To evaluate banana plants nutritional status and yield were sampled 30 plants in each treatment, totalizing 60 individuals in the experimental area. To evaluate nutritional status leaves were collected in the flowering period, and the amounts of macro and micronutrients were determined in plant tissue. The evaluated physical attributes did not differ as a function of soil depth, except penetration resistence that, from depth of 30 cm became higher in the shallow soil, with highest value of 5.1 MPa. In the deep soil, fertility and nutritional status of plants showed better values. Roots attributes like number of diameter classes and maximum diameter were higher in deep soil, and minimal diameter was higher in the deep soil also. The bunch weight and yield were higher in deep soil. In general, chemical and physical attributes, root system attributes and nutritional status of banana plants were better in deep soil, reflecting in better crop yield and enabling greater economic rentability in the site.